Non-obstructive Azoospermia in Male with Y-Chromosome Microdeletion: A Case Report - Angellee, Jesselyn; Agustinus, Agustinus; Narulita, Pety; Hartanto, Markus Christian; William, William; Suharyani, Sally (Indonesian Andrology and Biomedical Journal, 2024)
Male factors have contributed to at least 50% of all infertility cases worldwide. Numerous factors causing male infertility have been identified, one of which is azoospermia due to genetic defects. The detection of Y-chromosome microdeletion may assist in diagnosing male infertility as well as predicting the success rate of testicular sperm extraction. A man in his mid-thirties visited the Andrology outpatient clinic at Dr. Soetomo General Hospital accompanied by his wife. They have been married for eight years and have had regular unprotected sexual intercourse, but pregnancy has never been achieved. The patient’s semen analyses showed azoospermia in three examinations conducted at different times. Follicle-stimulating hormone (FSH) and luteinizing hormone (LH) were significantly increased, and genetic screening showed microdeletion in the Azoospermia Factor b (AZFb) subregion. Y-chromosome microdeletion is the second most common genetic defect causing azoospermia after Klinefelter syndrome. The AZF region in the distal part of the Y chromosome plays a key role in regulating spermatogenesis. Mutation or loss of any subregions in this factor may affect spermatogenesis, with the worst outcome being azoospermia. Detailed examinations are important to determine the cause of azoospermia, which may assist a physician in choosing the appropriate management for this condition. Infertile men with Y-chromosome microdeletion face challenges in reproducing naturally. They may also need genetic counseling regarding the possibility of passing on this genetic defect to their offspring and information on how to prevent it.